1997
DOI: 10.1002/(sici)1097-0215(19970717)72:2<265::aid-ijc11>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Genetics as a diagnostic tool in sarcomatoid renal-cell cancer

Abstract: Renal-cell cancer comprises a heterogeneous group of tumors, which currently can be sub-divided into morphologically distinct entities, each characterized by a specific combination of genetic changes. Sarcomatoid transformation might occur in any of the sub-types, resulting in tumors consisting of both carcinomatous and sarcomatous components. The specific diagnosis of these neoplasms, as to tumor sub-type, is usually made on the histologic properties of the carcinomatous tissue present. However, this might no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…51 The genetic abnormalities associated with the evolution of a spindle-cell morphology are poorly understood, although losses of chromosome 4q, 6q, 8p, 9, 13q, 14 and 17p, and gains of chromosome 5, 12, and 20 have been noted. 54,55 In a separate study gains of chromosome 1, 2, 6, 10, and 17 have been demonstrated for chromophobe sarcomatoid carcinoma. 56 There is also evidence to indicate that carcinomas evolve into sarcomatoid carcinomas through a variety of mutational steps as collagen expression of carcinomas showing early spindle-cell change differs from that of well-developed sarcomatoid carcinomas.…”
Section: Sarcomatoid and Rhabdoid Differentiationmentioning
confidence: 90%
“…51 The genetic abnormalities associated with the evolution of a spindle-cell morphology are poorly understood, although losses of chromosome 4q, 6q, 8p, 9, 13q, 14 and 17p, and gains of chromosome 5, 12, and 20 have been noted. 54,55 In a separate study gains of chromosome 1, 2, 6, 10, and 17 have been demonstrated for chromophobe sarcomatoid carcinoma. 56 There is also evidence to indicate that carcinomas evolve into sarcomatoid carcinomas through a variety of mutational steps as collagen expression of carcinomas showing early spindle-cell change differs from that of well-developed sarcomatoid carcinomas.…”
Section: Sarcomatoid and Rhabdoid Differentiationmentioning
confidence: 90%
“…Loss of heterozygosity at 3p25, gains of chromosomes 7 and 10, and an isochromosome 17q are among the few cytogenetic aberrations identified in early, low-stage sporadic clear cell renal cell carcinomas (RCCs) (Anglard et al, 1991;Dijkhuizen et al, 1997;Elfving et al, 1997;Wada et al, 1997). Advanced RCCs are characterized by hyperdiploidy or marked aneuploidy, with chromosomal aberrations involving all autosomes and with nonrandom changes most commonly mapped to 1p, 2q, 3p, 5q, 6q, and 8p (Mitelman, 1994;Presti et al, 1996;www.ncbi.nlm.mitelmansum.cgi).…”
Section: Introductionmentioning
confidence: 99%
“…Within this group, a subset is encountered with chromosomal translocations involving the Xp11region, mostly a (X;1)(p11;q21) translocation. There is accumulating evidence that these tumors de®ne a distinct subgroup of renal cell cancers with a relatively early age of onset and a lower male-female preponderance as compared to other renal cell cancers (Tonk et al, 1995;Dijkhuizen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%